Developing second language oral ability in foreign language classrooms: The role of the length and focus of instruction and individual differences. (21st July 2015) - SAITO, KAZUYA; HANZAWA, KEIKO
ABSTRACT: The current study aimed to examine how instruction can impact the global, segmental, prosodic, and temporal qualities of second language (L2) oral ability in foreign language (FL) settings (i.e., a few hours of target language input per week). Spontaneous speech was elicited via a timed picture description task from 56 Japanese freshman college students who had studied English through FL instruction from Grades 7 to 12 without any experience abroad. The tokens were rated for global accentedness and then submitted to segmental, prosodic, and temporal analyses. According to statistical analyses, (a) the participants' oral performance widely varied in relation to the length and focus of FL instruction, the frequency of their conversations in the L2, and aptitude; and (b) their diverse proficiency levels were predicted in particular by the amount of extra FL activities inside (i.e., pronunciation training) and outside (i.e., cram school) of high school (but not junior high) classrooms. The results in turn suggest that whereas extensive FL instruction (>875 hr) itself does make some difference in L2 oral ability development, its pedagogical potential can be increased by how students optimize their most immediate FL experience beyond the regular syllabus.